Tablet-Based Assessment of Cognitive Function Among Heart Failure Patients. Issue 3 (29th April 2022) - Urban, Szymon; Horożaniecka, Paulina; Włodarczak, Szymon; Błaziak, Mikołaj; Jura, Maksym; Zymliński, Robert; Biegus, Jan; Siennicka, Agnieszka
Abstract : Background: Cognitive impairment accompanying heart failure (HF) is an additional HF comorbidity, which may potentially affect the patient's self-care and compliance. We aimed to assess cognitive function (CF) using an application with games created as a cognitive training tool for children and adults, applied using a tablet, and to compare the results obtained by HF patients with the results obtained by healthy age-matched controls. Methods: A total of 69 individuals (49 HF patients and 10 healthy controls) were assessed using 4 games dedicated to measuring cognitive skills as well as questionnaires regarding their socioeconomic status. Additionally, HF patients were asked about their quality of life and anxiety and depression. Results: HF patients demonstrated worse results in each game assessing their cognitive functions as compared to the healthy age-matched controls, which is consistent with the previous studies on CF in HF. We have also noticed interesting patterns of relations between CF and sleep and education. Conclusions: We have demonstrated that information and communication technology devices can be successfully applied as feasible tools for cognitive assessment in the HF population. This is important as tablet-based CF assessment can be done on a large population without the involvement of trained personnel.